Addressing Mental Health Crises: A Collaborative Approach between Emergency Medical Services and Nursing in Prehospital Settings - Wayel Omair Saleh Altowaijri,; Nasser Tuaymis Muqbil Alharbi,; Rakan Saad Bin Turki Alharbi,; Muqrin Saad Turki Alharbi,; Faisal Awadh Nami Alharbi,; Faisal Musaad Awadh Alharbi,; Ayman Mohammed Sulaiman Alfowzan,; Khalid Saleem Khuwayshan Almutairi,; Ziyad Saad Alanazi,; Abdulmajeed Rabeh Atiah Alrashdi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Mental health crises represent a significant challenge in prehospital care, with Emergency Medical Services (EMS) often serving as the first point of contact for individuals experiencing psychiatric distress. This paper explores the importance of a collaborative approach between EMS providers and nurses in addressing mental health crises effectively in the prehospital setting. Through enhanced communication, joint training, and structured protocols, EMS and nursing professionals can improve patient outcomes, de-escalate crises, and ensure appropriate care. This manuscript highlights key strategies for successful collaboration, discusses the role of each discipline in crisis intervention, and advocates for a comprehensive approach to mental health crises that promotes safety, effective care, and patient well-being.